Hubungan Penggunaan Media Sosial “Jakarta Tourism” dengan Minat Berkunjung Followers - Muhammad Rasyid; O. Hasbiansyah (Bandung Conference Series: Communication Management, 2023)
Abstract. The Instagram account "Jakarta Tourism" namely @jakarta_tourism is an official account directly managed by the DKI Jakarta Provincial Disparekraf which provides information about tourist destinations, and events/events that are currently/will be held in Jakarta. This research was conducted to find out the relationship between the use of "Jakarta Tourism" social media and the interest in visiting followers on the Instagram account @jakarta_tourism. This study uses the S-R theory which is based on the assumption that behavior changes occur depending on the quality of the stimulus that communicates with the organism. Then, the method used in this study is quantitative with a correlational approach. Sampling using simple random sampling technique. The population in this study were followers of the Instagram account @jakarta_tourism, with a sampling technique using the Taro Yamane formula and the results obtained were 100 respondents. The measurement scale in this study is the ordinal scale. The validity test uses the Pearson Product Moment correlation analysis and the reliability test uses the Cronbach's Alpha test technique which is calculated using the SPSS application.The results of this study are (1) there is a relationship between context on the use of social media Instagram @jakarta_tourism and the interest in visiting followers, (2) there is a relationship between communication on the use of social media @jakarta_toursim and the interest in visiting followers, (3) there is a relationship between collaboratin on use of social media @jakarta_toursim with interest in visiting followers, (4) there is a relationship between connection on social media use @jakarta_toursim and interest in visiting followers. Abstrak. Akun Instagram “Jakarta Tourism” yaitu @jakarta_tourism adalah akun resmi yang langsung dikelola oleh Disparekraf Provinsi DKI Jakarta yang menyajikan informasi mengenai destinasi wisata, dan event/acara yang sedang/akan terselenggara di Jakarta. Penelitian ini dilakukan untuk mengetahui Hubungan Penggunaan Media Sosial “Jakarta Tourism” Dengan Minat Berkunjung Followers pada akun Instagram @jakarta_tourism. Penelitian ini menggunakan teori S-R yang mendasarkan asumsi yang mana perubahan perilaku terjadi tergantung kepada kualitas rangsangan (stimulus) yang berkomunikasi dengan organisme. Lalu, metode yang digunakan dalam penelitian ini adalah kuantitatif dengan pendekatan korelasional. Pengambilan sampel menggunakan teknik simple random sampling. Populasi dalam penelitian ini adalah followers akun Instagram @jakarta_tourism, dengan teknik pengambilan sampel menggunakan rumus Taro Yamane dengan dan hasil yang didapat sebesar 100 responden. Skala pengukuran dalam penelitian ini adalah skala ordinal. Uji validitas menggunakan analisis korelasi Product Moment Pearson dan uji reliabilitas dengan teknik uji Cronbach’s Alpha yang dihitung menggunakan aplikasi SPSS. Hasil dari penelitian ini adalah (1) terdapat hubungan antara context pada penggunaan media sosial Instagram @jakarta_tourism dengan minat berkunjung followers, (2) terdapat hubungan antara communication pada penggunaan media sosial @jakarta_toursim dengan minat berkunjung followers, (3) terdapat hubungan antara collaboration pada penggunaan media sosial @jakarta_toursim dengan minat berkunjung followers, (4) terdapat hubungan antara connection pada penggunaan media sosial @jakarta_toursim dengan minat berkunjung followers.